Dental Implant Placement in Patients on Bisphosphonate Therapy: a Systematic Review - Rokas Gelazius; Lukas Poskevicius; Dalius Sakavicius; Vaidas Grimuta; Gintaras Juodzbalys (Stilus Optimus, 2018)
Objectives: The review aims to study dental implant placement purposefulness for patients who have been treated or are on treatment with bisphosphonate medication. Material and Methods: Structured search strategy was applied on electronic databases: MEDLINE, PubMed, PubMed Central and ResearchGate. Scientific publications in English between 2006 and 2017 were identified in accordance with inclusion, exclusion criteria. Publication screening, data extraction, and quality assessment were performed. Outcome measures included implant failure or implant-related osteonecrosis of the jaw. Results: In total, 32 literature sources were reviewed, and 9 of the most relevant articles that are suitable to the criteria were selected. Heterogeneity between the studies was found and no meta-analysis could be done. Five studies analysed intraoral bisphosphonate medication in relation with implant placement, three studies investigated intravenous bisphosphonate medication in relation with implant placement and one study evaluated both types of medication given in relation with implant placement. Patients with intraoral therapy appeared to have a better implant survival (5 implants failed out of 423) rate at 98.8% vs. patients treated intravenously (6 implants failed out of 68) at 91%; the control group compared with intraoral bisphosphonate group appeared with 97% success implant survival rate (27 implants failed out of 842), showing no significant difference in terms of success in implant placement. Conclusions: Patients treated with intravenous bisphosphonates seemed to have a higher chance of developing implant-related osteonecrosis of the jaw. The intraorally treated patient group appeared to have more successful results. Implant placement in patients treated intraorally could be considered safe with precautions.